Atopy and allergic diseases among Saudi young adults: A cross-sectional study - Jobran Miree Alqahtani (Journal of International Medical Research, 2020)
Objective In this cross-sectional study, we aimed to determine the prevalence of asthma and other allergic diseases among a homogenous group of students attending the health colleges of a Saudi university and to investigate the relationship between their atopy profile and associated clinical symptoms of allergic diseases. Methods A total of 222 students completed the International Study of Asthma and Allergies in Childhood questionnaire and underwent skin prick testing (SPT) using a standardized panel of allergenic extracts. Results Overall prevalence of physician-diagnosed allergic diseases was 27% for bronchial asthma (BA), 13.1% for atopic dermatitis (AD), and 5% for allergic rhinitis (AR). Atopy was present in 90 (40.5%) students. Students with atopic disease were more likely to have physician-diagnosed BA, AR, and AD. Atopy and polysensitization was more frequent among male than female students. SPT results were positive in 20.8% of participants for Bermuda grass, 18.9% for cat fur, and 12.7% for Dermatophagoides pteronyssinus . Conclusion The prevalence of atopy and allergic diseases in Saudi young adults is high and worrisome. Comorbid allergic diseases were more prevalent among our participants with atopic disease. Determination of allergen sensitization patterns in patients with atopic disease is crucial for selecting proper preventive and therapeutic strategies.